THE EXPRESSIVE FUNCTION OF CRIMINAL PUNISHMENT: BETWEEN SOCIAL DISAPPROVAL AND JUSTICE BALANCE - Elena Oancea, (PEOPLE: International Journal of Social Sciences, 2025)
This article examines the expressive function of criminal punishment as a symbolic communication tool through which society conveys its disapproval of criminal behavior. It analyzes how the severity of sanctions reflects the degree of moral blame attributed to the offense and the risks posed by public pressure, including disproportionate punishment and penal populism. The study employs a theoretical methodology, reviewing contemporary literature on retributivism, communicative theories of punishment, and comparative criminal justice models, with emphasis on Nordic systems. Findings show that sanctions can combine practical effectiveness—crime prevention and social protection—with symbolic expression, respecting proportionality and supporting offender reintegration. The article also discusses the limitations of the expressive function, particularly its potential impact on stigmatization and the tension between moral blame and utilitarian objectives. Conclusions highlight the need for an integrated approach, where criminal sanctions express social condemnation while promoting rehabilitation, reparation, and social cohesion. This perspective provides a framework for developing fair criminal policies that convey a clear moral message without compromising proportionality or human dignity.